Control of Varroa destructor Mite Infestations at Experimental Apiaries Situated in Croatia - Ivana Tlak Gajger; Lidija Svečnjak; Dragan Bubalo; Tomislav Žorat (Diversity, 2019)
Experimental varroacidal treatments of honey bee colonies were conducted on five apiaries (EA1−EA5) situated at five different geographical and climatic locations across Croatia. The aim of this study was to assess the comparative efficacy of CheckMite+ (Bayer, Germany), Apiguard (Vita Europe Ltd.; England), Bayvarol, C, (Bayer, Germany), Thymovar, (Andrma BioVet GmbH, Germany), and ApiLife Var, (Chemicals Laif SPA; Vigonza, Italy) for controlling the honey bee obligatory parasitic mite Varroa destructor in different conditions in the field during summer treatment. The relative varroa mite mortality after treatments with applied veterinary medicinal products were EA1 (59.24%), EA2 (47.31%), EA3 (36.75%), EA4 (48.33%), and EA5 (16.78%). Comparing the relative efficacy of applied varroacides, the best effect was achieved with CheckMite+, and the lowest for honey bee colonies treated with Apiguard (statistically significant difference was confirmed; p < 0.05). Considering the lower efficacy of thymol-based veterinary medicinal products observed on all EA in these study conditions, it may be concluded that their use is limited under different treatment regimes. Despite unfavourable weather and environmental conditions, with exceptions of EA5/EA5′ and EA1, the relative varroacidal efficacy of authorized veterinary medicinal product treatments in moderately infested honey bee colonies ensured normal overwintering and colony development during next spring.